Risk factors for irreversible organ damages in peri- and postmenopausal women with systemic lupus erythematosus - S. Yu. Shkireeva; E. G. Zotkin; O. M. Lesnyak (Современная ревматология, 2018)
Objective: to identify irreversible organ damages and factors influencing their development and to compare existing musculoskeletal injuries with the activity of systemic lupus erythematosus (SLE).Patients and methods. The investigation enrolled 197 peri- and postmenopausal female outpatients (mean age, 50.94±9.1 years) with SLE, who were followed up at Clinical Rheumatology Hospital Twenty-Five, Saint Petersburg. The mean disease duration was 9.7±7.5 years. Cytostatic and glucocorticoid (GC) treatment regimens and dosages in the examinees were analyzed on the basis of their primary medical records. The investigators assessed the current disease activity by the SLE Disease Activity Index (SLEDAI-2K) and the Lupus Low Disease Activity State (LLDAS) and irreversible organ damages by the Systemic Lupus International Collaborating Clinics (SLICC) Damage Index (DI).Results and discussion. 93.4% of the patients continued to receive GS therapy at the time of inclusion in the study. The median GS maintenance dose was 12.5 mg/day. Almost half of the patients (n=86/43.7%) were in menopause (its mean duration was 12.8±7.1 years). Half of the examinees were noted to have remission (n=36/18.3%) or low SLE activity (n=92/46.7%) according to the SLEDAI-2K. Fifty-seven (28.9%) patients met all 5 LLDAS criteria; at the same time other 96 (48.7%) patients met 4 out of the 5 criteria, the 5th criterion being a high GC maintenance dose. High DI scores of ≥4 were found in two thirds (n=131/66.5%) of the examinees. Musculoskeletal system injuries ranked first among other disorders: osteoporosis (OP) and muscle weakness were detected in 76 (38.6%) and 69 (35.0%) patients, respectively. Regression analysis involving all statistically significant factors showed that the degree of damage was influenced by age (p=0.013215), total GS dose (p=0.000047), and previous therapy with cyclophosphamide (p=0.041505).Conclusion. The contribution of GS therapy to irreversible damage accrual is obvious in peri- and postmenopausal women with SLE. Timely dose adjustment or complete withdrawal of GS during remission in SLE is one of the key factors that substantially reduce the risk of progression of irreversible organ damages due to the prevention of OP and osteoporotic fractures in these patients.